Tetrahydrobiopterin Plays a Functionally Significant Role in Lipogenesis in the Oleaginous Fungus Mortierella alpina - Wang, Hongchao; Zhang, Chen; Chen, Haiqin; Gu, Zhennan; Zhao, Jianxin; Zhang, Hao; Chen, Yong Q.; Chen, Wei (Frontiers in Microbiology, 2020)
Tetrahydrobiopterin (BH4) is well known as a cofactor of phenylalanine hydroxylase (PAH) and nitric oxide synthase (NOS), but its exact role in lipogenesis is unclear. In this study, the GTP cyclohydrolase I (GTPCH) gene was overexpressed to investigate the role of BH4 in lipogenesis in oleaginous fungus Mortierella alpina. Transcriptome data analysis reveal that GTPCH expression was upregulated when nitrogen was exhausted, resulting in lipid accumulation. Significant changes were also found in the fatty acid profile of M. alpina grown on medium that contained a GTPCH inhibitor relative to that of M. alpina grown on medium that lacked the inhibitor. GTPCH overexpression in M. alpina (the MA-GTPCH strain) led to a sevenfold increase in BH4 levels and enhanced cell fatty acid synthesis and poly-unsaturation. Increased levels of nicotinamide adenine dinucleotide phosphate (NADPH) and upregulated expression of NADPH-producing genes in response to enhanced BH4 levels were also observed, which indicate a novel aspect of the NADPH regulatory mechanism. Increased BH4 levels also enhanced phenylalanine hydroxylation and nitric oxide synthesis, and the addition of an NOS or a PAH inhibitor in the MA-GTPCH and control strain cultures decreased fatty acid accumulation, NADPH production, and the transcript levels of NADPH-producing genes. Our research suggests an important role of BH4 in lipogenesis and that the phenylalanine catabolism and arginine–nitric oxide pathways play an integrating role in translating the effects of BH4 on lipogenesis by regulating the cellular NADPH pool. Thus, our findings provide novel insights into the mechanisms of efficient lipid biosynthesis regulation in oleaginous microorganisms and lay a foundation for the genetic engineering of these organisms to optimize their dietary fat yield.